2004
DOI: 10.1105/tpc.104.026963
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Pollen-S Function in Two Self-Compatible Selections of Prunus avium Is Associated with Deletion/Mutation of an S Haplotype–Specific F-Box Gene

Abstract: Recently, an S haplotype-specific F-box (SFB) gene has been proposed as a candidate for the pollen-S specificity gene of RNase-mediated gametophytic self-incompatibility in Prunus (Rosaceae). We have examined two pollen-part mutant haplotypes of sweet cherry (Prunus avium). Both were found to retain the S-RNase, which determines stylar specificity, but one (S 3 9 in JI 2434) has a deletion including the haplotype-specific SFB gene, and the other (S 4 9 in JI 2420) has a frame-shift mutation of the haplotype-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
187
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(200 citation statements)
references
References 47 publications
7
187
0
1
Order By: Relevance
“…Earlier studies have reported that two SFB alleles, SFB 1 and SFB 2 , are present in peach (Tao et al 2007). Here, two additional alleles, SFB 3 and SFB 4 , have been identified in peach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier studies have reported that two SFB alleles, SFB 1 and SFB 2 , are present in peach (Tao et al 2007). Here, two additional alleles, SFB 3 and SFB 4 , have been identified in peach.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that loss of self-incompatibility in Prunoideae is mainly attributed to pollen-part mutation. In self-compatible cultivars of sweet cherry and apricot, for example, DNA insertions/deletions as well as point mutations have been detected in SFB genes (Sonneveld et al 2005;Vilanova et al 2006;Marchese et al 2007). However, the finding that stylar part mutation results in self-compatible phenotype has also reported in almond (Ferna´ndez i Martı´et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Naturally occurring and induced S-locus mutants have proved to be a valuable resource in studies of homomorphic SI systems (Goring et al, 1993;Nasrallah et al, 1994;Sassa et al, 1997;Golz et al, 2000Golz et al, , 2001Ushijima et al, 2004;Sonneveld et al, 2005;Hauck et al, 2006). In heteromorphic SI systems, the genes determining distyly and tristyly have not yet been discovered (Barrett and Shore, 2008;Labonne et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The self-incompatibility reaction is triggered when the S gene is expressed in the pollen (SFB gene) and pistil (S-RNasa gene), which stops pollen tube growth. Knowledge of the genetic and molecular bases of the self-incompatible reaction has allowed the application of molecular techniques such as PCR amplification of S alleles with consensus or specific primers that amplify the two introns, which are part of the sequence of the S-RNasa gene (Tao et al, 1999;Tobutt et al, 2001;Wiersma et al, 2001;Sonneveld et al, 2001;Wünsch and Hormaza, 2004;Sonneveld et al, 2006), or amplify regions of the SFB gene (Sonneveld et al, 2005). The peach is self-fertile; in contrast, most cultivated Prunus species, such as cherry, almond, plums, and apricot, are self-infertile and therefore self-incompatible.…”
Section: Molecular Markersmentioning
confidence: 99%